Upaya Guru Mengoptimalkan Penggunaan Media Audiovisual dalam Pembelajaran Seni Budaya (Tari) Kelas VII C SMPN 35 Kerinci - Aisyah Jesika; Alrizka Hairi Dilfa (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
The purpose of this research is to evaluate the methods implemented by the teacher and their impact on students' understanding and dance skills. The method used is qualitative research, including direct observation, interviews with teachers, and analysis of the audiovisual materials used. The results of the study show that the use of audiovisual media in dance education increases students' interest and motivation, as well as improves their learning outcomes. This media helps explain the material more effectively and makes learning more engaging. The application of this method has also proven effective in enhancing students' self-confidence, such as encouraging them to try new things, take responsibility for tasks, and participate actively in discussions. In conclusion, audiovisual media plays an important role in supporting the teaching and learning process. However, there are some challenges faced, such as limited equipment and teachers' knowledge. It is recommended that schools provide adequate equipment and that teachers continue to develop their skills in using educational media to achieve optimal results.